2017
DOI: 10.1111/1440-1681.12681
|View full text |Cite
|
Sign up to set email alerts
|

Zinc oxide nanoparticles as a novel anticancer approach; in vitro and in vivo evidence

Abstract: Currently, the outcomes of conventional chemotherapeutic approaches are unsatisfactory. Clinical application of nanoparticles seems promising. We aim to evaluate the possible antitumor activity of zinc oxide nanoparticles (ZnONPs) as a chemotherapeutic approach in in vitro and in vivo experimental models. An in vitro study was performed on three different cell lines, namely human hepatocellular carcinoma (HEPG2), human prostate cancer (PC3), and none-small cell lung cancer (A549) cell lines. An in vivo study u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
40
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(47 citation statements)
references
References 51 publications
(57 reference statements)
5
40
0
Order By: Relevance
“…This was evidenced by a significant decrease in CAT and GPx activities, as well as increase of NO and MDA levels in animals treated with DENA. These findings are in agreement with previous studies reporting that DENA‐induced oxidative stress plays a significant role in hepatocarcinogenesis …”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This was evidenced by a significant decrease in CAT and GPx activities, as well as increase of NO and MDA levels in animals treated with DENA. These findings are in agreement with previous studies reporting that DENA‐induced oxidative stress plays a significant role in hepatocarcinogenesis …”
Section: Discussionsupporting
confidence: 93%
“…These findings are in agreement with previous studies reporting that DENA-induced oxidative stress plays a significant role in hepatocarcinogenesis. 29,[40][41][42] Interestingly, the current study found that tiopronin protected against DENA-induced HCC. We observed an improvement in the liver functions, a significant decrease in the relative liver weight and serum AFP level in addition to the alleviation of the macro-and microscopic features of HCC after tiopronin administration.…”
Section: Ta B L Ementioning
confidence: 45%
See 2 more Smart Citations
“…ZnO NPs or ZnO-composites are applied for vaccine adjuvant use because the particulate form of NPs can efficiently deliver antigens to dendritic cells with subsequent adequate inflammatory responses [27, 28]. ZnO NPs have also been proposed as therapeutic agents in cancer [2931] and inflammation [32]. However, the direct contact of ZnO NPs with blood components such as platelets can be critical in some instances, involving platelet activation and thrombus generation, but there is little information about the impact of size and surface functionalization of ZnO NPs on platelet homeostasis.…”
Section: Discussionmentioning
confidence: 99%